HUMAN RESOURCES MANAGEMENT BUSINESS ETHICS REVIEW AT PT XYZ - Sebastian, Linda (Dinasti International Journal of Management Science, 2020)
Business ethics in managing Human Resources (HR) is very necessary because it is related to humans. Where every human being has the right to receive fair treatment, regardless of ethnicity, race or religion. PT XYZ is a startup that is engaged in the culinary industry. With a number of employees above 500 people, managing HR in accordance with business ethics is crucial. This research was conducted using descriptive qualitative method. The result is that PT XYZ has generally carried out HR management in accordance with business ethics. But PT XYZ still has tasks such as establishing workers' organizations and making regulatory pocketbooks